Water injection as a way for pollution control - Michael Fratita (Elsevier, 2021)
The continuous development of internal combustion engines has been permanently limited by pollutant emissions. Hence, in Europe, EURO pollution norms have been implemented, and constantly updated, becoming more restrictive in order to minimize pollution in the major urban areas. Water injection is one of the strategies being explored to improve engine efficiency. However, there is need to assess its influence on pollutant emissions. The paper aims to track the impact of water injection in reducing pollutant emissions. The present study was performed on a spark ignition side-valve engine with a water injection system in the intake manifold at constant load and engine speed, and various values for the ratio between water and fuel (W/F) ranging from 0.25 to 1.0 were tested. The tests were performed for two compression ratios of 7.8 and 11.7. CO, CO2, HC, and NOx emissions were tracked depending on the ignition advance. The maximum advance for each case is set by the knock limit.